Prevalence and risk factors associated with SARS-CoV-2 infection among workers of Instituto Nacional de Salud del Niño, Peru, April 2020 to March 2021 - Romero Ramos, Cesar Walter (2023)
Objective: To determine the prevalence and risk factors associated with SARS-CoV-2 infection among workers of Instituto Nacional de Salud del Niño (INSN) from April 2020 to March 2021. Materials and methods: A non-experimental, descriptive, cross-sectional study. The sample consisted of 608 workers who tested positive for COVID-19 using a rapid antigen test. The COVID-19 clinical-epidemiological research sheets prepared bythe Ministry of Health of Peru and self-administered by the workers were reviewed. The INSN Department of Epidemiology staff verified the completion of the sheets. The data was entered into a database, which was used for the respective statistical analysis. The study was approved by the INSN Institutional Research Ethics Committee (registration code: PI-17/21). Results: COVID-19 prevalence among INSN workers was 7.24 % from April 2020 to March 2021. Out of the workers with COVID-19 71.4 % were women; 83.4 % were in the 30 to 59 age range with an average age of 44.71 years; 65.6 % were healthcare workers, most of whom were nursing technicians; and 56.9 % experienced symptoms, mainly fever/chills (12.2 %), cough (8.9 %), malaise (7.7 %), sore throat (6.7 %), stuffy nose (2.5 %) and headache (1.3 %). Most workers lived in Lima Centro districts (33.2 %). A significant association between sex, age groups, worker type and worker profile was found. Conclusions: COVID-19 prevalence among INSN workers was 7.24 %; the most frequent characteristics, which showed significant differences with the rest of the factors, were being a woman, healthcare worker and nursing technician. A total of 56.9 % of the workers experienced symptoms, only 20.9 % developed clinical signs and 10.9 % had comorbidities.